Analisis Hukum Islam Terhadap Jual Beli Sawah Garapan di Desa Megulung Kidul Kabupaten - Saifudin, Saifudin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This research discusses the practice of leasing with limited time sale and purchase agreements and additional time on the latest jobs. The author sees this incident as common in Megulung Kidul Village, with the assumption that if the practice and contract are replaced by leasing, the community must use the leasing principle, which in the last time cultivating the fields cannot be added to the time period.  This study aims to determine whether the sale and purchase of fertile rice fields in Megulung Kidul Village, Pituruh Subdistrict, Purworejo Regency is in accordance with Islamic Economic Law. This research includes a case study. Data obtained through buyers and sellers through interview observations, and also documentation. Apart from sellers and buyers, also through literature such as books and documents such as books, journals or relevant sources as references in this thesis. The theory used in this discussion is the leasing theory in the perspective of Islamic law and ʻurf. The result of this research is that the sale and purchase of rice fields is allowed to be carried out on the condition that the contract used is changed by leasing. The sale and purchase of arable rice fields is classified as 'urf fasid' because it is seen from the point of view of the additional activities made at the end of the cultivation of the fields.